Magnifico - Violett Films, Inc. (Manila Unico Entertainment, 2002)
The story of a poor young boy named Magnifico who makes all the preparations for the burial of his grandmother, and tries to find solutions to the problems of his family and neighbors, which gives hope and happiness to them in the end.
Based on the grand prize winning piece in the 2001 Screenplay Writing Contest sponsored by the Film Development Foundation of the Philippines.
DVD.
Story & screenplay, Michiko Yamamoto ; directed by Mario J. delos Reyes.
Lorna Tolentino, Albert Martinez, Jiro Manio.
Keywords: Families -- Philippines -- Feature films; Poor children -- Philippines -- Feature films